Impact of the invasive seaweed Asparagopsis armata on coastal environments - Silva, Carla Ofélia Ferreira da (2021)
The introduction of invasive species has been increasing with globalization and is recognized as one of the main threats to the oceans and the second cause of biodiversity loss. The red alga Asparagopsis armata exhibits a strong invasive behavior inducing significant changes in the invaded community. The study of the impact of this invasive on ecologically relevant species is crucial for risk assessment. Assessing sub-organismal endpoints may therefore provide early indicators of A. armata exposure and their possible impacts on natural populations. The results emphasize the importance of considering specific (biomarkers) as well as more generalized and ecologically related in situ responses to identify and evaluate biological effects of A. armata in the field. To validate the fatty acid profile (FAP) tool, the marine snail G. umbilicalis was exposed to three metals: cadmium, nickel and mercury, and the total lipid content, lipid peroxidation and FAP were measured. The FAP analysis suggested a change in fatty acid metabolism and indicated a link between exposure to metals and homeoviscous adaptation and immune response. In particular, five fatty acids (palmitic, eicosatrienoic, arachidonic, eicosapentaenoic, and docosahexaenoic acids) proved to be good indicators of the responses of G. umbilicalis to the metals used, thus having the potential to be used as biomarkers for contamination by metals in this species. In the continued use of this species, there was also a need to characterize it biochemically. To assess the different enzymatic forms present in the sea snail, different substrates and selective inhibitors were used. Additionally, in vitro and in vivo effects of the pesticide chlorpyrifos (CPF) on AChE activity were investigated, along with effects on snails' behaviour. The results obtained showed that G. umbilicalis has cholinesterases with characteristics of AChE. In addition, CPF inhibited AChE activity both in vitro and in vivo conditions, and AChE inhibition was positively correlated with flipping test. To understand the mechanisms of toxicity of the invasive A. armata, lethal and sublethal effects of A. armata were investigated and biochemical biomarkers responses associated with energy metabolism were analyzed.Results showed invertebrates’ physiological status impairment after exposure to this algae exudate. Highest concentrations of exudate significantly increased lipid content in both organisms. In the shrimp, protein content, ETS, and LDH were also significantly increased. On the contrary, these parameters were significantly decreased in G. umbilicalis. Behavioural impairments were observed in G. umbilicalis exposed to A. armata exudate, with reduction in feeding consumption and increased flipping time. Antioxidant defences, oxidative damage and neuronal parameter as well as the fatty acid profile were evaluated after exposure to A. armata exudate. Results revealed different metabolic responses between species, indicating that A. armata exudate affected the organisms through different pathways. Despite previous studies indicating that the exudate effected G. umbilicalis’ survival and behaviour, this does not seem to result from oxidative stress or addressed neurotoxicity. For P. elegans, an inhibition of AChE and the decrease of antioxidant capacity with the increase of LPO, suggests neurotoxicity and oxidative stress as mechanisms of exudate toxicity for this species. For fatty acids, there were differences more pronounced for P. elegans with a general increase in PUFA, which commonly means a defence mechanism protecting from membrane disruption. Omega-3 PUFAs ARA and DPA were increased in both invertebrates. To evaluate the effects of this invasive in a more realistic scenario, Variations on native intertidal seaweed and macroinvertebrate assemblages inhabiting rock pools with and without the presence of the invasive macroalgae A. armata were assess. Results showed different patterns in the macroalgae composition of assemblages but not for the macrobenthic communities. Ellisolandia elongata was the main algal species affected by the invasion of A. armata. Invaded pools tended to show less species richness, showing a more constant and conservative structure, with lower variation of its taxonomic composition than the pools not containing A. armata. This work relied on the ecotoxicological and ecological information to provide insight in how A. armata affects specific invertebrates and in general coastal communities, embracing methods at different biological organization levels which prepare the way for various hypotheses testing in assessing Asparagopsis armata exudates toxicity. The analyses of biochemical biomarkers contribute to the knowledge of the sub lethal effects and ecological impacts on communities. Thus, aiding the comprehensive understanding of the mechanisms that lead to higher level responses.